The Effect of a Surface Combat Swimming Training Program on Swimming Performance - Kostoulas, Ioannis D.; Kounalakis, Stylianos N.; Toubekis, Argyris G.; Kaniadakis, Antonios; Karagiannis, Anastasios; Mavraganis, Dimitrios; Karatrantou, Konstantina; Gerodimos, Vassilis (International Journal of Sports Medicine, 2021)
In this study the effect of a surface combat swimming (sCS) training program on performance in freestyle swimming and sCS was examined. Forty-five officer cadets were divided into three equivalent groups: a control group (CG), a group that was trained only with a swimsuit and fins (SF), and a group that was trained with combat uniform and equipment (UE). Groups SF and UE followed a 60-min training program with sCS for 4 weeks, 4 times per week. Before and after the training program all groups performed 4×50 and 400-m freestyle swimming, 250-m sCS with a uniform and equipment, 350-m with a swimsuit and fins, and 300-m with a swimsuit. The UE group showed improved performance in 4×50-m (mean±SD 14±9 s) and in 250-m sCS (24±14 s) (p<0.01). Both the SF group and the UE group improved in 300-m sCS, in 350-m sCS and in 400-m freestyle (p<0.05). We conclude that the training adaptations seemed to be specific, not only with regard to the activity performed, but also in terms of the actual conditions of an operation, which also include equipment.
Keywords: adaptations, equipment, military activities